DIPLOMATIC CUSTOMS IN THE PERSPECTIVE OF FORMAL SOURCES OF LAW - POPESCU, Corina Florence (International Journal of Legal and Social Order, 2022)
Custom is considered a formal source of law, but this interpretation and qualification varies from one national system to another, depending on the national system's membership of the major legal systems. In public international law, custom has been maintained as the source of this branch of law, especially in the field of diplomatic law, an aspect that is also the object of this study.